2020
DOI: 10.7565/ssp.v3.4498
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on the Impact of Different Presentations of Maternal Depression on Children's Socio-Emotional Development

Abstract: Background: Maternal depression from the perinatal period onwards is associated with an increased likelihood of suboptimal socio-developmental outcomes in offspring, with increasing interest in the extent to which sustained maternal depression impacts on these associations. The current protocol outlines the methodology of a systematic review to synthesise the evidence on the impact of maternal depression from the perinatal period onwards and offspring socio-emotional development, defined as internalising, exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [46]. Details of the study protocol can be found in Morales [47] and the PRISMA checklist in S1 Checklist.…”
Section: Protocolmentioning
confidence: 99%
“…This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [46]. Details of the study protocol can be found in Morales [47] and the PRISMA checklist in S1 Checklist.…”
Section: Protocolmentioning
confidence: 99%